Analysis Screening On Gen Y Throujh Black Campaign Issues Pilpres 2014 In Indonesia - Moh. Alimuddin (STID Raudlatul Iman Sumenep, 2019)
This study identified the censorship effect black campaign pilpres 2014 issue on cognitive, affective and psychomotor change. This study focuses on the memories, feelings and actions using news clip on black campaign pilpres 2014 issue. This study has three main objectives: The first objective is to identify the effects of cognitive, affective effects and psychomotor effects. The second objective is to analyse the effects of cognitive, affective and psychomotor. The third objective is to confirm Theory of Planned Behaviour 1988 as the theory in this study. This study used in experimental method. The analysis is conducted a quantitative analysis form of the test inference. The results obtained that impression news clip black campaign pilpres 2014 censorship issues affected public in terms of cognitive, affective and psychomotor. In addition, the study also found between changes in cognitive, affective and psychomotor, cognitive and affective are impressionable compared with psychomotor on audience. Therefore, the results of this study obtained that psychomotor effects more intractable than cognitive and affective caused of culture and identity of the audience, especially the Gen Y. Kajian ini mengenal pasti kesan penepisan isu black campaign pilpres 2014 terhadap perubahan kognitif, afektif dan psikomotor. Kajian ini memfokuskan kepada ingatan, perasaan dan tindakan dengan menggunakan tayangan klip berita penapisan isu black campaign pilpres 2014. pilpres 2014 yang berupa klip berita. Kedua menganalisis kesan kognitif, Kajian ini mempunyai tiga objektif utama. Pertama ialah mengenal pasti kesan kognitif, kesan afektif dan kesan psikomotor terhadap penapisan isu black campaign kesan afektif dan kesan psikomotor terhadap penapisan isu black campaign pilpres 2014 yang berupa klip berita. Ketiga mengesahkan Theory of Planned Behavior 1988 yang menjadi teori dalam kajian ini. Kaedah yang yang digunakan dalam kajian ini ialah eksperimen. Analisis kajian yang dijalankan dalam bentuk kuantitatif yaitu dengan menggunakan ujian analisis inferensi. Hasil kajian yang diperoleh bahwa tayangan klip berita penapisan isu black campaign pilpres 2014 mempengaruhi khalayak dari segi kognitif, afektif dan psikomotor. Selain itu, kajian juga mendapati ada perbedaan kesan antara perubahan kognitif, afektif dan psikomotor. Kognitif dan afektif lebih mudah berubah dan dipengaruhi berbanding dengan perubahan psikomotor khalayak. Dengan hasil kajian yang diperoleh menunjukkan bahawa kesan psikomotor lebih sukar dipengaruhi disebabkan oleh budaya dan identiti khalayak terutamanya kepada Gen Y.